A high-protein diet is anti-steatotic and has no pro-inflammatory side effects in dyslipidaemic APOE2 knock-in mice. Issue 8 (27th August 2014) - Garcia Caraballo, Sonia C.; Comhair, Tine M.; Dejong, Cornelis H. C.; Lamers, Wouter H.; Köhler, S. Eleonore
Abstract : High-protein (HP) diets are effective anti-steatotic treatment options for patients with non-alcoholic fatty liver disease, but whether these diets also decrease steatosis in hyperlipidaemic conditions is not known. The aim of the present study was to determine the effects of a HP diet on hepatic steatosis and inflammation in hyperlipidaemic mice. Hyperlipidaemic male and female APOE2 knock-in (APOE2ki) mice were fed a semi-synthetic low-protein (LP) or HP diet in combination with a low-fat diet or a high-fat diet for 3 weeks. The HP diets reduced hepatic fat and cholesterol concentrations to 40–55 % of those induced by the corresponding LP diets and attenuated hepatic inflammation mildly. The VLDL-associated plasma cholesterol concentrations decreased to 60–80 %, but those of TAG increased 3–4-fold. APOE2-mediated restriction of fat import into the liver did not modify the effects of a HP diet previously observed in wild-type mice. Female APOE2ki mice exhibited a higher expression of lipogenic, cholesterol-synthesising, inflammatory and cell-stress genes than wild-type female or male APOE2ki mice, but a similar response to HP diets. Low Apob expression and unchanged plasma APOB100 concentrations suggest that HP diets increase the plasma concentrations of TAG by slowing their clearance. The decrease in plasma leptin and hepatic fat and glycogen concentrations and the increase in fatty acid-oxidising gene and phosphoenolpyruvate carboxykinase 1 protein expression suggest a HP diet-mediated increase in mitochondrial metabolism. In conclusion, a HP diet reduces hepatic lipid content in dyslipidaemic mice and lowers the activation status of inflammatory cells in the liver.